The sound of music story eaudiobook How a beguiling young novice, a handsome austrian captain, and ten singing von trapp children inspired the most beloved film of all time. - Santopietro, Tom (Tantor Media, 2015)
On March 2, 1965, "The Sound of Music" was released in the United States and the love affair between moviegoers and the classic Rodgers and Hammerstein musical was on. Rarely has a film captured the love and imagination of the moviegoing public in the way that "The Sound of Music" did as it blended history, music, Austrian location filming, heartfelt emotion and the yodeling of Julie Andrews into a monster hit. Now, Tom Santopietro has written the ultimate "Sound of Music" fan book with all the inside dope from behind the scenes stories of the filming in Austria and Hollywood to new interviews with Johannes von Trapp and others. Santopietro looks back at the real life story of Maria von Trapp, goes on to chronicle the sensational success of the Broadway musical, and recounts the story of the near cancellation of the film when the "Cleopatra" bankrupted 20th Century Fox.